2012
DOI: 10.1080/02643944.2012.688063
|View full text |Cite
|
Sign up to set email alerts
|

Stress and anxiety surrounding forthcoming Standard Assessment Tests in English schoolchildren

Abstract: The Standard Assessment Tests (SATs) taken by pupils in their final year of primary schooling in England have been widely criticised for placing children under too pressure and contributing to an increase in test-related stress and anxiety. In this exploratory study we set out to explore the experiences of forthcoming SATs in a small sample of children using an appraisal model of stress and to reflect on whether these criticisms are justified. Results from focus groups with pupils and interviews with class and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…However, teachers may also communicate other messages about the value, importance, and worth of examinations through their instructional dialogue (Banks & Smyth, 2015;Hall, Fear appeals, subjective task value, and academic self-efficacy Collins, Benjamin, Nind, & Sheehy, 2004;Gulek, 2003;Putwain, Connors, Woods, Nicholson, 2012). These messages are used to highlight how failure can lead to subsequent negative life opportunities (e.g., difficulty in finding a job or continuing in education or training) as a motivational tactic to encourage students to engage with their studies (Putwain & Roberts, 2009).…”
Section: Messages Used Prior To High-stakes Examinationsmentioning
confidence: 99%
“…However, teachers may also communicate other messages about the value, importance, and worth of examinations through their instructional dialogue (Banks & Smyth, 2015;Hall, Fear appeals, subjective task value, and academic self-efficacy Collins, Benjamin, Nind, & Sheehy, 2004;Gulek, 2003;Putwain, Connors, Woods, Nicholson, 2012). These messages are used to highlight how failure can lead to subsequent negative life opportunities (e.g., difficulty in finding a job or continuing in education or training) as a motivational tactic to encourage students to engage with their studies (Putwain & Roberts, 2009).…”
Section: Messages Used Prior To High-stakes Examinationsmentioning
confidence: 99%
“…In this study, we examine resilience in relation to performance on statutory tests taken at the end of primary schooling in England. Research has suggested that these tests are considerable sources of pressure and anxiety for children due to their pervasive influence on the design of teaching and learning (Hall, Collins, Benjamin, Nind, & Sheehy, 2004) and the importance of educational achievement for pupils' self-worth judgments (Putwain, Connors, Woods, & Nicholson, 2012). As research has also shown that pupils experience greater anxiety in high-stakes tests (Connor, 2001(Connor, , 2003Segool, Carlson, Goforth, von der Embse, & Barterian, 2013) we would argue that the stakes of these tests are sufficiently high to present a pressured testing situation under which resilient children are able to withstand more effectively.…”
Section: Resilience and Academic Performancementioning
confidence: 99%
“…A student's perceptions can also influence other similar constructsdfor example, test anxiety (Hembree, 1988)dand differences in test anxiety have been reported at both lower (Putwain et al, 2012) and higher (Naveh-Benjamin et al, 1997) educational levels. Some students look forward to tests or examinations because they want to demonstrate their skills and knowledge, which could be a facilitating aspect of test anxiety (Alpert and Haber, 1960).…”
Section: Introductionmentioning
confidence: 99%